PENERAPAN APFIQRO (AKTIVITAS PEMELAJARAN FIQIH DAN IQRO) BERBASIS EDUKASI PADA TPA AL-MUTTAQIN - Abdi, Muhammad Alim; Aji, Fery Setyo; A?ayunnisa, Nurul; Ulhaq, Muhammad Dhiya; Hayati, Lilis Nur; Irawati, Irawati; Herman, Herman (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
Al-Quran education is a non-formal educational institution with a type of Islamic religionaimed at providing teaching reading the Al-Quran, understanding the basic knowledge of Islamin early childhood. TPA Al-Muttaqin as a PKM-M activity partner has quite a lot of studentsfrom early childhood. The lack of teaching staff and the methods used in teaching santri weremonotonous by confronting the students one by one to justify their reading, so there were onlya few students when they were studying and more students played due to lack of supervision.The aim of PKM-M is to increase the understanding of santri regarding the learning ofjurisprudence and iqro, to give understanding and knowledge to teachers and parents of santriby conducting counseling and socialization as well as mentoring technological knowledge inlearning. The PKM-M team uses a learning by doing system method with educational-basedteaching media. First, counseling activities for giving material. Second, training activities toteach coaches and instructors in implementing educational media in learning. Third, evaluationmonitoring activities. So the results increase the understanding of santri regarding fiqh and iqrolearning, add insight and knowledge to teachers and santri parents related to the application ofeducational media.